Large‐scale migrations of brown bears in Eurasia and to North America during the Late Pleistocene - Anijalg, Peeter; Ho, Simon Y. W.; Davison, John; Keis, Marju; Tammeleht, Egle; Bobowik, Katalina; Tumanov, Igor L.; Saveljev, Alexander P.; Lyapunova, Elena A.; Vorobiev, Alexandr A.; Markov, Nikolai I.; Kryukov, Alexey P.; et al. (Journal of Biogeography)
2018